Features of mechanical alloying process for obtaining powder charge materials based on the Fe-Cu-C System - Внуков, Александр Александрович (Technology audit and production reserves, 2015)
The use of different alloying methods for the powder steel production is discussed and some results of original research in this field are given in the article. The main purpose of the study is obtaining a powder charge based on iron with the highest level of physical and technological properties. The use of modern diagnostic tools for properties of materials allows researchers to collect and analyze information received from experts around the world, with support for decision-making in the field of materials with a unique set of physical and mechanical characteristics. The prerequisites for use of mechanosynthesis for alloying powder constructional steels are discussed in the article. The complex of physical and technological properties of the powder mix on the basis of iron for production of sintered structural products alloying with copper and carbon is investigated. The presented methodology for assessing the properties of the powder mix allows receiving real information with the use of modern methods of analysis of the performance complex of structural materials based on iron. The methodology of the research is designed to select the most optimal method of alloying powder constructional steels produced by powder metallurgy. We propose to use a mechanosynthesis method for alloying powder constructional steels. The research results can be applied by experts, metallurgists and machine builders to create a new class of materials with high performance.